UTILIZING PICTURES IN INCREASING PUPILS` VOCABULARY MASTERY IN AN EFL CLASS IN PALU CITY INDONESIA - Marzuki, Abdul Gafur (Musawa: Journal for Gender Studies, 2018)
This research aimed at analyzing the implementation of pictures technique in increasing vocabulary of the fourth grade pupils of SDN 6 Palu. This research employed a collaborative classroom action research design and was implemented in the form of cycles consisting of four major steps: planning, implementing, observing and reflecting. The subject of the research were 34 pupils of grade four B at SDN 6 Palu. The instruments used to collect data were test, observation checklists, field notes, and questionnaire. This research was completed in two cycles because the results of the research in the first cycle did not meet the criteria of success. Each of cycle comprises four meetings. The findings of the research showed that the applying of technique in teaching English can increase pupils` vocabulary mastery. This is shown by the improvement of the mean score made by the pupils, that is: 7.04 in cycle I to 8.10 in Cycle II and the number of the pupils who got scores at least 6.5 or greater was 22 (64.71%) in cycle I to 34 (100%) in cycle II. In addition, the pupils gave positive response toward the model applied as reflected from the results of three variables of measurement of the questionnaire given: learning motivation, learning result, and tasks accomplishment. It can be concluded that the pictures technique is effective and applicable in teaching vocabulary.